HIV-1 Vaccine-Induced C1 and V2 Env-Specific Antibodies Synergize for Increased Antiviral Activities - Pollara, Justin (American Society for Microbiology, 2014)
The RV144 ALVAC/AIDSVax HIV-1 vaccine clinical trial showed an estimated vaccine efficacy of 31.2%. Viral genetic analysis identified a vaccine-induced site of immune pressure in the HIV-1 envelope (Env) variable region 2 (V2) focused on residue 169, which is included in the epitope recognized by vaccinee-derived V2 monoclonal antibodies. The ALVAC/AIDSVax vaccine induced antibody-dependent cellular cytotoxicity (ADCC) against the Env V2 and constant 1 (C1) regions. In the presence of low IgA Env antibody levels, plasma levels of ADCC activity correlated with lower risk of infection. In this study, we demonstrate that C1 and V2 monoclonal antibodies isolated from RV144 vaccinees synergized for neutralization, infectious virus capture, and ADCC. Importantly, synergy increased the HIV-1 ADCC activity of V2 monoclonal antibody CH58 at concentrations similar to that observed in plasma of RV144 vaccinees. These findings raise the hypothesis that synergy among vaccine-induced antibodies with different epitope specificities contributes to HIV-1 antiviral antibody responses and is important to induce for reduction in the risk of HIV-1 transmission. IMPORTANCE The Thai RV144 ALVAC/AIDSVax prime-boost vaccine efficacy trial represents the only example of HIV-1 vaccine efficacy in humans to date. Studies aimed at identifying immune correlates involved in the modest vaccine-mediated protection identified HIV-1 envelope (Env) variable region 2-binding antibodies as inversely correlated with infection risk, and genetic analysis identified a site of immune pressure within the region recognized by these antibodies. Despite this evidence, the antiviral mechanisms by which variable region 2-specific antibodies may have contributed to lower rates of infection remain unclear. In this study, we demonstrate that vaccine-induced HIV-1 envelope variable region 2 and constant region 1 antibodies synergize for recognition of virus-infected cells, infectious virion capture, virus neutralization, and antibody-dependent cellular cytotoxicity. This is a major step in understanding how these types of antibodies may have cooperatively contributed to reducing infection risk and should be considered in the context of prospective vaccine design.